Comparison of Post-Operative Pain in Patients Undergoing Percutaneous Nephrolithotomy receiving Oral Post-Operative Analgesia Augmented by Bupivacaine versus Post-Operative Intravenous Analgesia Alone - Jawed, Muhammad Usman; Ali, Adnan; Umair , Musab; Shirazi, Syed Hamza; Alam, Nauman (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare peri-tract infiltration of Bupivacaine augmented by oral post-operative analgesia versus post-operative intravenous analgesia alone in patients undergoing percutaneous nephrolithotomy in terms of mean post-operative pain score. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Urology Rawalpindi, Pakistan from Apr to Oct 2019. Methodology: Total number of 68 patients planned for percutaneous nephrolithotomy were randomly divided into two equal groups with 34 patients in each group by lottery method. Group-A patients received peri-tract local anesthesia infiltration with 0.25% Bupivacaine while group-B patients received post-operative intra-venous analgesia. Both groups were compared in terms of postoperative pain scores. Results: The mean pain score as per visual analogue scale at 1 hour was 4.53±0.62 in Group-A vs 5.21±0.85 in group-B with p=0.004. The mean score of pain at 3 hours was 3.85±0.50 in group-A vs 6.79±0.73 in group-B with p˂0.001. The mean score at 6 hours was 3.38±0.78 in group-A vs 6.03±0.90 in group-B with p˂0.001. The mean pain score at 12 hours was 1.21±0.77 in group-A vs 5.26±0.99 in group-B with p˂0.001. Conclusion: Peri-tract infiltration of Bupivacaine was associated with significantly less postoperative pain as compared to standard intravenous analgesia in patients undergoing percutaneous nephrolithotomy.